Estimates of Household Sector Wealth for South Africa, 1970-2003. - Aron, J; Muellbauer, J (Wiley, 2006)
Market values of components of household sector wealth are important explanatory variables for aggregate consumer expenditure and household debt in macro-econometric models. We construct the first coherent set of the main elements of household-sector balance sheet estimates at market value for South Africa. Our quarterly estimates derive from published data on financial flows, and other capital market data, often at book value. Our methods rely, where relevant, on accumulating flow of funds data using appropriate benchmarks, and, where necessary, converting book to market values using appropriate asset price indices. Relating asset to income ratios for various asset classes to asset price movements and other features of the economic environment, throws light on the changing composition of household sector wealth. Most striking are the relative rise in the value of pension wealth and the trend decline of directly held securities, the decline and recent recovery of housing wealth, and the rise in household debt and concomitant decline of liquid assets from the early 1980s to the late 1990s.